해수 내 다양한 알루미늄 선박용 재료의 캐비테이션 진폭에 따른 캐비테이션-침식 손상 연구 - 양예진; Ye-jin Yang; 김성종; Seong-jong Kim (Corrosion science and technology, 2020)
Recently, 5000 series and 6000 series Al alloys have been used as hull materials for small and medium-sized ships because of their excellent weldability, corrosion resistance, and durability in marine environments. Al ships can navigate at high speed due to their light weight. However, cavitation-erosion problems cause reducing durability of Al ship at high speed. In this investigation, 5052-O, 5083-H321, and 6061-T6 Al alloy materials were used to evaluate the damage characteristics with amplitude (cavitation strength). As a result of the electrochemical experiments, the corrosion current density and corrosion potential of 6061-T6 in seawater were 8.52 × 10 -7 A/cm 2 and -0.771 V, respectively, presenting the best corrosion resistance. The cavitation-erosion experiment showed that 5052-O had the lowest hardness value and cavitation-erosion resistance. 5052-O also had a very short incubation period. As the experiment progressed for 5052-O, pitting formed and grew in a short time, and was observed as severe cavitation-erosion damage that surface detached. Among the three specimens, 5083-H321 presented the highest hardness value and the damage rate was the smallest after the initiation of pitting.